Characterisation of photonic crystals fabricated by holographic lithography - Dedman, E; Dedman, Emma Ruth (2004)
﻿ Holographic lithography is a new technique developed for the fabrication of threedimensional photonic crystals in polymer. Four coherent laser beams are interfered to generate a three-dimensionally periodic interference pattern in a film of photoresist. Subsequent processing steps render a three-dimensional photonic crystal, whose structure is commensurate with the original interference pattern. Two interference patterns are discussed in detail: a face-centred cubic pattern with a conventional lattice constant of 922nm in air and a face-centred cubic pattern with a conventional cube side of 397nm in air (interference wavelength 355nm). Three types of basis are presented for the interference pattern with a 922nm lattice constant: a righthanded, a left-handed and a non-chiral basis. Photonic crystals have been fabricated with both a chiral and a non-chiral basis and evaluated by scanning electron microscopy. Optical transmission measurements are presented for the non-chiral photonic crystals and are interpreted in both a Bragg scattering model and a photonic bandstructure model. A 'GaAs' and a 'diamond' basis are presented for the interference pattern with a 397nm lattice constant. Photonic crystals have been fabricated with the 'GaAs' basis and evaluated by scanning electron microscopy.